Sustainable livelihood for a better adaptation towards climate change among small scale fishermen in Malaysia - Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2018)
Adaptation towards climate change among the community has becoming a pressing issue, hence, effort to strengthen it has become a priority. It is recognized that not every adaptation strategy fit to every group of community, each of the groups have their own strength. In this study, the focus is placed on one of the important groups in Malaysia – the small scale fishermen whereby efforts are placed to strategize specific climate adaptation strategies via intensification of their livelihood assets. Initially, the paper looks on the background of fisheries industry in Malaysia, the small scale fishermen in Malaysia and the climate change scenario in Malaysia. Then, it gears the readers to the discussions on the impacts of climate change on the livelihood assets, the need to strengthen the assets, the relations between the assets and subsequently to the prime aim of the paper – the recommendations to strengthen the small scale fishermen climate adaptation via the intensification of their livelihood assets.